List of Spanish seamen (note)
[ ] Nottingham [ ] 39. Jose Larrabeiti London M.S. Prat Newc/t D G Zugasti L/pool E Larrazabal L/pool P Rodriguez Garcia Grimsby T. Marcos Garma Grimsby Eusebio Amesti Sunderland 292/946/25a/18